REVENUE COMPARATIVE ANALYSIS OF INTENSIVE AND SEMI INTENSIVE SHEEP BREEDER ON THE VILLAGES OF CELAWAN VILLAGE, PANTAI CERMIN SUBDISTRICT, SERDANG BEDAGAI REGENCY - Purnama Ketaren; I Sembiring; S Umar; A H Daulay; N D Hanafi (Talenta Publisher, 2017)
This study’s objective was to investigate the income and R / C of sheep business. This research was conducted on Cilawan Village,Pantai Cermin Sub District, Serdang Bedagai Regency, Sumatera Utara Province for 2 months starting from September until November 2017. The study was a survey which used Determination Method. Number of samples were 30% of total number of breeder in research area; there were 8 respondents whose intensive breeders and 30 respondents whose semi intensive breeders. The data used in this research were primary data and secondary data. Primary data were the result of interviews with respondents and secondary data were obtained from the Central Bureau of Statistics. The results showed that intensive breeder earned income smaller compared to semi intensive breeder. Income on every sheep sale was Rp 3.468.241,-on intensive and Rp 5.794.982,- on semi intensive breeder and the value of R/C was 0.144. The conclusion of this study that sheep breeding system in Celawan Village Regency consisted of two maintenance system, intensive and semi intensive system which gave different effect to farmer's income. This was because intensive maintenance systems required more costs for feed and labor costs compared to semi intensive system.